J22 Registry To Enroll-hd: Transition In Europe And The Founding Of A New Research Platform. (17th September 2014) - Fullam, R; Giuliano, J; Knipe, C
Abstract : Background: Enroll-HD, a global longitudinal observational study has been established to provide a research platform and clinical data set to support research into the aetiology of Huntington's disease (HD) and accelerate the development of novel therapeutics. In June 2012 the first patient was recruited to the study in North America. The study now covers 4 continents of which Europe is currently the principle region of growth and development. Aims: Building on the achievements of Registry, an existing European longitudinal data set, Enroll-HD will continue the data collection of prior Registry participants in addition to including new participants. Sites in all regions including Europe will collect Enroll-HD data using standardised operating procedures and study materials to ensure consistency of data collection. Methods: The transition of Registry to Enroll-HD necessitates 4 components. 1) Complete monitoring and close out of Registry data prior to transfer to Enroll-HD database. 2) Obtaining appropriate ethical, regulatory and data protection permissions across 20 countries and over 130 sites. 3) Provision of the electronic data capture (EDC) platform with language specific adaptions. 4) Training of site staff and monitors for Enroll-HD and provision of study materials. This effort is accomplished utilising the skills of a well-coordinated multi-disciplinary team with expertise in the areas of information technology, clinical operations, and legal and regulatory affairs. Results: The University of Ulm was the first European site to transition from Registry to Enroll-HD in December 2013. Since then, more than a fifth of sites have transitioned from multiple countries. Ethical Review Board, regulatory, and data protection permissions have been obtained in seven European Countries and applications are active in a further seven. The EDC provision for 16 countries has been established. Training of site staff and monitors is ongoing. To date approximately 500 participants have been recruited with 93% of core assessments complete. Conclusions: The transition from Registry to Enroll-HD is underway and gaining momentum. Over the coming year the European contribution to the Enroll-HD data set will grow and in partnership with sites around the globe, make Enroll-HD an unparalleled resource for HD research.